Study on the Performance of the Light Automatic Control Device. Issue 5 (February 2019) - Li, Zhiyong; Zhang, Sibin; Liu, Wei; Zhao, Yuqing; Gao, Jianling
Abstract: This paper presents a light automatic control device that can automatically adjust the sunlight indoors based on the solar radiation outdoors. This article researches the device's influence on indoor environment through experiments. Studies have shown that the illuminance of an experimental room with the device can be automatically adjusted according to solar radiation outdoors. When the solar radiation is strong, the illuminance of the experimental room about 30% lower than that of the comparison room which is not equipped with the device. When the solar radiation is weak, the illuminance of the experimental room is close to that of the comparison room. The difference between the indoor temperature of the experimental room and that of the comparison room also follows the similar rule. It is proved that the device can automatically regulate the sun light in room effectively, thereby achieving the control of indoor illumination and temperature so as to reduce the energy consumption in building.